Influence of the Microbiome on Chronic Rhinosinusitis With and Without Polyps: An Evolving Discussion - Huntley, Kyle S.; Raber, Joshua; Fine, Lauren; Bernstein, Jonathan A. (Frontiers in Allergy, 2021)
Chronic rhinosinusitis (CRS) is widely prevalent within the population and often leads to decreased quality of life, among other related health complications. CRS has classically been stratified by the presence of nasal polyps (CRSwNP) or the absence nasal polyps (CRSsNP). Management of these conditions remains a challenge as investigators continue to uncover potential etiologies and therapeutic targets. Recently, attention has been given to the sinunasal microbiota as both an inciting and protective influence of CRS development. The healthy sinunasal microbiologic environment is largely composed of bacteria, with the most frequent strains including Staphylococcus aureus, Streptococcus epidermidis, and Corynebacterium genera. Disruptions in this milieu, particularly increases in S. aureus concentration, have been hypothesized to perpetuate both Th1 and Th2 inflammatory changes within the nasal mucosa, leading to CRS exacerbation and potential polyp formation. Other contributors to the sinunasal microbiota include fungi, viruses, and bacteriophages which may directly contribute to underlying inflammation or impact bacterial prevalence. Modifiable risk factors, such as smoking, have also been linked to microbiota alterations. Research interest in CRS continues to expand, and thus the goal of this review is to provide clinicians and investigators alike with a current discussion on the microbiologic influence on CRS development, particularly with respect to the expression of various phenotypes. Although this subject is rapidly evolving, a greater understanding of these potential factors may lead to novel research and targeted therapies for this often difficult to treat condition.